1976
DOI: 10.1002/jpln.19761390304
|View full text |Cite
|
Sign up to set email alerts
|

Stability constants of complexes of humic and fulvic acids isolated from organic‐enriched Egyptian soils with Fe, Mn and Zn cations

Abstract: Stabilitätskonstanten von Fe‐, Mn‐ und Zn‐Komplexen mit Humin‐ und Fulvosäuren, die aus mit organischer Substanz angereicherten ägyptischen Böden isoliert wurden Humin‐ und Fulvosäuren wurden isoliert von Alluvial‐ und Kalkbodenproben, welche vorher mit verschiedenen anorganischen Rückständen angereichert waren. Die Verhältnisse von Metall zu Fulvo‐ und Huminsäuren und die Werte der Stabilitätskonstante der Metallkomplexe dieser Verbindungen mit Fe, Mn und Zn wurden bei pH 7 durch die Anwendung der Ionenaustau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1980
1980
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Several authors arrived at the conclusion that bidentate complexes (1 iron atom coordinated by 2 organic ligands) are formed (Elgala et al, 1976;Takahashi et al, 1997;Ghatak et al, 2004). At the highest Fe concentrations in Fig.…”
Section: Characteristics Of Fe-ha Interactionmentioning
confidence: 96%
“…Several authors arrived at the conclusion that bidentate complexes (1 iron atom coordinated by 2 organic ligands) are formed (Elgala et al, 1976;Takahashi et al, 1997;Ghatak et al, 2004). At the highest Fe concentrations in Fig.…”
Section: Characteristics Of Fe-ha Interactionmentioning
confidence: 96%
“…Additionally, stability constants were higher for zinc humic acid complexes than for zinc fulvic acid complexes for all pH. Elgala et al (1976) determined the log K values at pH 7 for zinc-humic and zincfulvic acid complexes to be 5.45 and 4.01, respectively. Schnitzer and Skinner (1966) concluded that it is not the number of bonds but their strength that determines the magnitude of stability constants.…”
Section: Effect Of Ph On the Release Of Zinc From Soilmentioning
confidence: 99%
“…The strength of the complexation reaction can be measured by evaluation of a conditional formation constant. (57)(58)(59)46).…”
Section: Organic -Inorganic Interactionsmentioning
confidence: 99%